1984
DOI: 10.1017/s0022215100146845
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculated pleomorphic adenoma of the tongue base manifesting with dysponea

Abstract: Pleomorphic adenomas of the minor salivary glands are rare. The most common site is in the palate. We have come across a case of pedunculated pleomorphic adenoma of the base of die tongue which came to us only when the tumour had caused respiratory distress. Case ReportK.D., a 35-year-old male patient, came to the Department of Otolaryngology and Head and Neck Surgery of B. Y. L. Nair Charitable Hospital with a complaint of dysphagia for three months. The dysphagia was gradually increasing and when he came to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Approximately 8% of pleomorphic adenomas occur in the minor salivary glands. The most frequent site is the palate (50%); the next common site is the upper lip, while the base of the tongue is a very rare one [2]. Of 1320 tumours reviewed by Chaudhary et al [3], the base of the tongue was the site of origin in only 1% of all intraoral minor salivary gland tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 8% of pleomorphic adenomas occur in the minor salivary glands. The most frequent site is the palate (50%); the next common site is the upper lip, while the base of the tongue is a very rare one [2]. Of 1320 tumours reviewed by Chaudhary et al [3], the base of the tongue was the site of origin in only 1% of all intraoral minor salivary gland tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology showed that the lesion in our patient was not a verrucous carcinoma but a typical well-differentiated squamous cell carcinoma. Although pedunculated forms of basaloid squamous cell carcinoma and spindle cell carcinoma, as well as adenocarcinoma and pleomorphic adenoma, have been observed on the tongue [13,[19][20][21][22][23], squamous cell carcinoma is more likely [6].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors of the salivary glands comprise 3% of all neoplasms [2]. The majority of salivary gland neoplasms are benign with pleomorphic adenomas being the most common.…”
Section: Discussionmentioning
confidence: 99%